2020
DOI: 10.1002/brb3.1493
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity predicts the dispositional use of expressive suppression but not cognitive reappraisal

Abstract: Introduction Previous research has identified specific brain regions associated with regulating emotion using common strategies such as expressive suppression and cognitive reappraisal. However, most research focuses on a priori regions and directs participants how to regulate, which may not reflect how people naturally regulate outside the laboratory. Method Here, we used a data‐driven approach to investigate how individual differences in distributed intrinsic functional brain connectivity predict emotion reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
2
10
2
Order By: Relevance
“…Our findings not only contrast with the two studies on which we based our a priori hypotheses (Uchida et al, 2015;Picó-Pérez et al, 2018), they also contradict several other studies that have identified patterns of intrinsic functional connectivity that differ between the dispositional use of ER strategies or are associated with experiential and neuronal reappraisal success (Morawetz et al, 2016;Pan et al, 2018;Burr et al, 2020). Common to these studies is that regions in the default mode network have been identified.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings not only contrast with the two studies on which we based our a priori hypotheses (Uchida et al, 2015;Picó-Pérez et al, 2018), they also contradict several other studies that have identified patterns of intrinsic functional connectivity that differ between the dispositional use of ER strategies or are associated with experiential and neuronal reappraisal success (Morawetz et al, 2016;Pan et al, 2018;Burr et al, 2020). Common to these studies is that regions in the default mode network have been identified.…”
Section: Discussioncontrasting
confidence: 99%
“…Common to these studies is that regions in the default mode network have been identified. Particularly, the latest study by Burr et al (2020) used the largest sample up to date (N = 1,316) in a data-driven, theory-free approach and found that intrinsic connectivity of the default mode network was associated with dispositional use of suppression (but not reappraisal). Critically, the authors used general functional connectivity (GFC, Elliott et al, 2019) to leverage shared features of task and restingstate fMRI and circumvent reported reliability issues of restingstate measures (e.g., Noble et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings not only contrast with the two studies on which we based our a priori hypotheses (Picó-Pérez et al, 2018;Uchida et al, 2015), they also contradict a number of other studies that have identified patterns of intrinsic functional connectivity that differ between the dispositional use of ER strategies, or are associated with experiential and neuronal reappraisal success (Burr et al, 2020;Morawetz et al, 2016;Pan et al, 2018). Common to these studies is that regions in the default mode network have been identified.…”
Section: Discussioncontrasting
confidence: 99%
“…Common to these studies is that regions in the default mode network have been identified. Particularly, the latest study by Burr et al (2020) used the largest sample up to date (N = 1316) in a data-driven, theory-free approach and found that intrinsic connectivity of the default mode network was associated with dispositional use of suppression (but not reappraisal). Critically, the authors used general functional connectivity (GFC, Elliott et al, 2019) to leverage shared features of task and resting-state fMRI and circumvent reported reliability issues of resting state measures (e.g., Noble, Scheinost, & Constable, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analytic evidence based on functional neuroimaging studies demonstrates that women display stronger emotional reactivity to negative stimuli than men (Filkowski et al, 2017;Stevens and Hamann, 2012). Questionnaire-based studies have shown that men have a greater tendency to use habitual expressive suppression (Gross and John, 2003;Haga et al, 2009) and there is evidence that the neural basis of expressive suppression differs between men and women (Burr et al, 2019;Wang et al, 2017). Given these differences, it is unclear to what extent the findings of the studies included in this systematic review can be generalized to men.…”
Section: Sample Compositionmentioning
confidence: 99%